Measuring airports’ ability to sustain the COVID-19 disruption in the Chinese domestic market: Considering the effect of low-cost carriers and high-speed rails - Weicheng Wang; Xiangru Wu; Xiaowen Fu; Kun Wang (Transport Economics and Management)
Air transportation continues to gain focus and grow rapidly to meet the demand for social development. Meanwhile, the risk of unpredictable disruptive events like the COVID-19 pandemic must be addressed to ensure stable air transportation. The Chinese domestic market was experiencing unique challenges during the pandemic, considering strict pandemic control measures, limited deregulation, and significant competition from high-speed rail (HSR). This study evaluates the determinants of Chinese airports' performance from 2020 to 2022 based on a weighted connectivity index and an interactive fixed effect (IFE) model. We highlight the critical role of low-cost carriers (LCCs) in mitigating the pandemic's impact, with LCC route entry demonstrating a more pronounced positive effect on airport performance than increased flight frequency. Contrary to conventional expectations, HSR availability did not significantly undermine airport performance, suggesting a more complex air-HSR relationship shaped by intermodal cooperation and regional travel behaviour. Geographical heterogeneity also played a significant role: while LCC entry was vital in the less-developed western regions, increased frequency of LCC flights contributed more to the stable and mature eastern markets. These findings underscore the importance of fostering LCC development and promoting air-HSR coordination. Overall, this study provides valuable insights for policymakers and industry stakeholders to enhance the resilience of the aviation sector in the post-COVID-19 era.